2019
DOI: 10.1186/s41687-019-0158-6
|View full text |Cite
|
Sign up to set email alerts
|

The expansion and validation of a new upper extremity item bank for the Patient-Reported Outcomes Measurement Information System® (PROMIS)

Abstract: BackgroundThe Patient-Reported Outcomes Measurement Information System® (PROMIS) includes a Physical Function (PF) item bank and an Upper Extremity (UE) item bank, which is composed of a subset of items from the PF bank. The UE item bank has few items and known ceiling effects. Therefore, this study aimed to expand the item bank to assess a wider range of functioning. With the additional content, other psychometric properties—improved content validity, item bank depth, range of measurement, and score reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…This is likely due to somewhat more heterogeneity of content in the PF item bank relative to the other banks and selection of PF items that emphasize mobility over other concepts such as upper extremity function and flexibility. 26,30,31 Investigators often ask how much statistical power a given test will have in a planned study or experiment. These short forms were constructed to maximize their precision and efficiency in clinical samples, estimated to be 1 SD worse than the general population.…”
Section: Identification Of the Item Sets For Each Promis Domainmentioning
confidence: 99%
“…This is likely due to somewhat more heterogeneity of content in the PF item bank relative to the other banks and selection of PF items that emphasize mobility over other concepts such as upper extremity function and flexibility. 26,30,31 Investigators often ask how much statistical power a given test will have in a planned study or experiment. These short forms were constructed to maximize their precision and efficiency in clinical samples, estimated to be 1 SD worse than the general population.…”
Section: Identification Of the Item Sets For Each Promis Domainmentioning
confidence: 99%
“…However, while the sample size used in the present study was adequate for investigating DIF [29,43,44], it was rather small for robust CFA results [45], potentially causing lack of sensitivity to detect multidimensionality. Several other studies have questioned whether different PROMIS PF domains are indeed measuring a unidimensional construct [7,21,42,46,47]. Moreover, upper body items are less informative compared with other PROMIS PF items, also indicating a distinct upper extremity construct [9].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, upper body items are less informative compared with other PROMIS PF items, also indicating a distinct upper extremity construct [9]. In consequence, some authors have suggested to use separate upper extremity and mobility item banks, which are provided by PROMIS [26,42,47].…”
Section: Discussionmentioning
confidence: 99%
“…Because we deemed a sample of at least 500 patients mandatory for item parameter estimation, data of studies performed by van Bruggen et al [17] and Haan et al [16] were pooled [18]. To study measurement invariance for language, we used additional data of US patients from an online panel, aged 18 years or older, who endorsed having some difficulty due to UE pain or function [15].…”
Section: Participantsmentioning
confidence: 99%
“…PROMIS included an item bank that measures UErelated physical functioning and this bank has recently been updated, from v1.2 to v2.0, to measure a wider range of upper extremity functioning and showed higher precision when used in patients with UE disorders [15]. The v2.0 item bank was translated into Dutch-Flemish (DF-PROMIS-UE v2.0) and some of the psychometric properties of this bank have been studied in patients with UE disorders from a general [16] and an academic hospital [17].…”
Section: Introductionmentioning
confidence: 99%